Histamine Content In Processed Bullet Tuna (Auxis thazard) Stew With Various Concentration Of NaCl - Hattu, Nikmans; Telussa, Ivonne; Fransina, Eirene G.; Seumahu, Cecelia A. (Indonesian Journal of Chemical Research, 2014)
Analysis of histamine content in processed bullet tuna (Auxis thazard) stew flesh can be carried out by Spectrophotometry method, using p- phenildiazonium sulfonate reagent. A qualitative, visual comparison of colour intensity of samples with reference colour scale of the standard solution concentration can be used to determine levels of histamine without the aid of a spectrophotometer. The histamine content is determined quantitatively by the standard curve regression equation (y= 0.003x–0.062) with determination coefficient value (R2= 0.938). The results showed that histamine content inprocessed bullet tuna (Auxis thazard) obtained: 46.9964; 40.3093; 34.4348; 28.9900 and 24.8862 mg/100g fish, at 0.5; 1.0; 1.5; 2.0 and 2.5% concentration of NaCl, respectively.